2012
DOI: 10.1111/jdv.12032
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of digital dermoscopy follow‐up of melanocytic skin lesions: a study on behalf of the International Dermoscopy Society

Abstract: It has been demonstrated that dermoscopic monitoring of melanocytic lesions allows for the recognition of melanoma in early stages while minimizing the excision of benign lesions. However, it is still pending to determine the real impact of digital follow-up in the clinical management of pigmented lesions. To assess the evidence of follow-up of melanocytic skin lesions with digital dermoscopy in the management of individuals at risk for melanoma by performing a meta-analysis. Medline database was screened, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
129
2
25

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 44 publications
(187 reference statements)
6
129
2
25
Order By: Relevance
“…Bu zor hastalarda ancak digital dermoskopik izlem gereksiz eksizyon oranını azaltabilir. Bir nevüsün digital dermoskopik izleminde değişim varlığı, melanomu çok erken-belki de melanomun klinik ve dermoskopik olarak tanınmasının güç olduğu aşamada tanısını mümkün kılabilirken, izlemde stabil olması gereksiz eksizyon oranını azaltmaktadır 8 . Digital dermoskopik izlem, kısa dönem veya uzun dönem izlem şeklinde yapılabilir.…”
Section: Dermoskopi/dijital Dermoskopi Konusunda öZelleşmiş Bir üNiteunclassified
See 3 more Smart Citations
“…Bu zor hastalarda ancak digital dermoskopik izlem gereksiz eksizyon oranını azaltabilir. Bir nevüsün digital dermoskopik izleminde değişim varlığı, melanomu çok erken-belki de melanomun klinik ve dermoskopik olarak tanınmasının güç olduğu aşamada tanısını mümkün kılabilirken, izlemde stabil olması gereksiz eksizyon oranını azaltmaktadır 8 . Digital dermoskopik izlem, kısa dönem veya uzun dönem izlem şeklinde yapılabilir.…”
Section: Dermoskopi/dijital Dermoskopi Konusunda öZelleşmiş Bir üNiteunclassified
“…Yüksek riskli gruptaki hastalar için uzun dönem digital dermoskopik izlem önerilmelidir. "Yüksek risk grubu" dışındaki riskli hastalar ve lezyonunda değişim öyküsü olan veya atipisi belirgin lezyonları olan hastalar için ise kısa dönem izlem önerilebilir 8 . Özellikle yüksek risk grubu hastalarda yapılacak izlemler, dermoskopi/dijital dermoskopi konusunda özelleşmiş bir ünite gerektirir.…”
Section: Dermoskopi/dijital Dermoskopi Konusunda öZelleşmiş Bir üNiteunclassified
See 2 more Smart Citations
“…Long-term follow-up is used for the surveillance of patients with atypical mole syndrome or high nevi count among other risk factor. 10 Haenssle et al recommend follow-up every 3 months for patients with familial atypical mole and melanoma syndrome (FAMM) and every 6-12 months for those with multiple atypical nevi. 12 Argenziano et al and Salerni et al in two independent studies have found that in 58,3-65% of patients with slow growing melanoma the only dermocopic abnormality was enlargement of the lesion (more than 2 mm in 3 years -Argenziano et al).…”
Section: Dermoscopy (And Videodermoscopy)mentioning
confidence: 99%